The Competitive Strategy of the Video-Sharing Platform ---A Case Study of Youtube - Lai, Yifei (Transactions on Economics, Business and Management Research, 2024)
Nowadays, with the development of the Internet, video-sharing platforms have become increasingly important in the entertainment lives of the modern generation. As the largest video platform in the world, YouTube has dominated the market due to its unique competitive strategies, which provide a significant reference value for other video platforms in the industry. Some researchers have analyzed the various competitive strategies of video platforms in different aspects, but there is still a research gap in the specific analysis of YouTube as a case study for investigating the competitive strategies in the video platform industry. This essay reveals the competitive advantages and strategies of YouTube and the relationship between them, through the methodology of literature review and case analysis. The results show that the competitive advantages of YouTube include a market-leading position and technological advantages. Based on these advantages and in order to maintain them, YouTube has adopted various competitive strategies, including adequate technical support and investment, unique business models, and product innovation. Therefore, the competitive advantages and competitive strategies of YouTube are mutually beneficial.